2012
DOI: 10.1002/jcb.23406
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of alcohol and aldehyde dehydrogenases in melanoma cells and in melanocytes

Abstract: Disturbances in vitamin A metabolism are an important attribute of some cancer cells. Most evidence point that these disturbances lead to decreasing of the retinoic acid concentration in tumor cells. Up to now, in benign and malignant skin cells the features of vitamin A metabolism with its participating enzymes are not entirely understood. Alcohol and aldehyde dehydrogenases (ALDH) are involved in the retinol metabolism, oxidizing retinol, and retinal in retinoic acid or reducing retinal in retinol. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Diminished ATRol esterification occurs in response to reduced LRAT expression or activity in various cancer cells (17)(18)(19)(20)(21)(22)(23). Recently, we identified human melanoma-specific alterations in the expression and activity of enzymes participating in retinoid metabolism (24,25). Interestingly, we found high LRAT expression and activity in human melanoma cells but not in benign melanocytes (25).…”
Section: Introductionmentioning
confidence: 83%
“…Diminished ATRol esterification occurs in response to reduced LRAT expression or activity in various cancer cells (17)(18)(19)(20)(21)(22)(23). Recently, we identified human melanoma-specific alterations in the expression and activity of enzymes participating in retinoid metabolism (24,25). Interestingly, we found high LRAT expression and activity in human melanoma cells but not in benign melanocytes (25).…”
Section: Introductionmentioning
confidence: 83%
“…Regulation of retinoid metabolism is complex [1,5,6], and aberrant vitamin A metabolism in cancer cells could represent a potential retinoid resistance mechanism in tumor cells. Accordingly, both the synthesis and metabolism of the bioactive metabolites of ATRol are sometimes impaired in cancer cells [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that cancer-specific modulations in retinoid metabolism reduce ATRA levels in cancer cells and that both the synthesis and metabolism of the bioactive metabolites of retinol are impaired in cancer cells relative to normal cells [10,11]. Recently, we identified alterations in retinoid metabolism in human melanoma cells [6,20]. ATRol can be oxidized to ATRA or alternatively be esterified into biologically inactive retinyl esters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider it possible that a defect in aldehyde dehydrogenase leads, after 2 days of occlusion, to the topical accumulation of toxic substances such as acetaldehyde. The presence of these enzymes in the skin is well known (7,8,9), and deficiency in these enzymes leads to non-immunological irritant skin reactions (10)(11)(12)(13). With an occlusively applied 100% isopropanol solution, there might be sufficient substrate to provoke such an irritant reaction to acetaldehyde in predisposed individuals.…”
mentioning
confidence: 99%